PENGARUH KOMPOSISI BAHAN PUPUK ORGANIK CAIR DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL JAGUNG MANIS (ZEA MAYS SACCHARATA L.) - Hadiyanti, Nugraheni; Probojati, Rasyadan Taufiq; Anindita, Devina Cinantya; Nareswari, Aptika Hana Prastiwi (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2022)
Sweet corn (Zea mays saccharata L.) is an important food commodity with high economic value. Sweet corn has a high business opportunity because of its fast production age and high selling value. The experiment was conducted to study the effect of the interaction between the composition of liquid organic fertilizer and plant spacing on the growth and yield of sweet corn. The experiment has designed in a factorial randomized block design (RAK) with two factors and three repetitions. The first factor is the composition of liquid organic fertilizer consists of 4 levels, namely: cow urine 42%, coffee skin 58% (P0); cow urine 35%, coffee skin 65% (P1); cow urine 72%. coffee skin 28% (P2); cow urine 21%, coffee skin 79% (P3). The second factor is the spacing, which consists of 3 levels, namely: 20x20 cm (J1); 30x30cm (J2); 40x40 cm (J3). Data analysis used variance and continued with the smallest significant difference test (BNT) at 5% level if the results were significantly different. The combination of liquid organic fertilizer composition and plant spacing affects the number of leaves and the length of the cob. Sweet corn with POC (72% cow urine, 28% coffee husk) and 30x30 cm spacing was able to produce 12,933 leaves. Combination of POC ingredients (21% cow urine and 79% coffee skin); 40x40 cm resulted in the length of the cob an increase of 1.5%. There was an interaction between the composition of liquid organic fertilizer and plant spacing on plant height, but the results were not significantly different. Sweet corn plants using 21% POC from cow urine and 79% coffee husk with a spacing of 40x40 cm produced cobs weight per plot of 240.27 grams and 208.22 grams, respectively. Keywords: sweet corn, spacing, material composition, liquid organic fertilizer